2019
DOI: 10.1002/jclp.22743
|View full text |Cite
|
Sign up to set email alerts
|

The necessity, validity, and clinical utility of a new diagnostic entity: Acute suicidal affective disturbance

Abstract: Objective: Here we argue for the necessity, validity, and clinical utility of a new diagnostic entity, acute suicidal affective disturbance (ASAD).Method: We expand on the conceptual, clinical, and practical rationale for ASAD, propose its defining features, describe research results to date, and suggest avenues for future research.Results: There is accruing evidence for the existence of a previously unclassified, rapid-onset mood disturbance that geometrically escalates and regularly results in life-threateni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 73 publications
0
27
0
6
Order By: Relevance
“…ASAD criteria include four primary features: a drastic, acute increase in suicidal intent, marked social alienation or self-alienation, hopelessness, and over-arousal (i.e., insomnia, irritability, or agitation). Initial research demonstrates ASAD's validity, reliability, and utility ( 150 , 169 ). SCS includes five primary components: entrapment, affective disturbance, loss of cognitive control, hyperarousal, and social withdrawal.…”
Section: General Recommendations and Possible Alternatives For Suicidmentioning
confidence: 99%
“…ASAD criteria include four primary features: a drastic, acute increase in suicidal intent, marked social alienation or self-alienation, hopelessness, and over-arousal (i.e., insomnia, irritability, or agitation). Initial research demonstrates ASAD's validity, reliability, and utility ( 150 , 169 ). SCS includes five primary components: entrapment, affective disturbance, loss of cognitive control, hyperarousal, and social withdrawal.…”
Section: General Recommendations and Possible Alternatives For Suicidmentioning
confidence: 99%
“…Acute Suicidal Affective Disturbance (ASAD) is based on empirical pre-suicidal clinical features and theory-driven predictors ( 13 , 17 , 19 ) ( Table 2 ). This concept emphasizes that symptoms develop very quickly.…”
Section: Acute Suicidal Affective Disturbance and Suicidal Crisis Synmentioning
confidence: 99%
“…While these are clinically important features, they alone provide little useful information on the background of suicidal behavior (e.g., mental disorder, crisis situation, etc.) and do not help to identify warning signs or acute risk and to predict future suicidal behavior ( 12 , 13 ). Because acute suicide risk usually develops rapidly (up to some days or hours) ( 14 ), it would be necessary to introduce a category that emphasizes the characteristics of this life-threatening pre-suicidal state of mind requiring urgent intervention ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, nearly 70% of adolescents in one retrospective study reported that thoughts of suicide began just 30 min before their most recent suicide attempt (Negron, Piacentini, Graae, Davies, & Shaffer, 1997). Several proposed clinical diagnoses such as the Suicide Crisis Syndrome (Schuck, Calati, Barzilay, Bloch-Elkouby, & Galynker, 2019) and Acute Suicidal Affective Disturbance (Rogers, Chu, & Joiner, 2019) also include aspects of episodic crisis-like states of intense suicidal thinking (in addition to other states, e.g., agitation) appearing imminently before suicidal behavior. Despite the theoretical support, retrospective empirical work, and earlier calls to do so (Glenn & Nock, 2014), there has been no prospective work exploring the minutes and hours right before a suicide attempt.…”
Section: Novel Research Questionsmentioning
confidence: 99%